NFTs AND THE LEGAL LANDSCAPE : A NEW FRONTIER IN INTELLECTUAL PROPERTY, DIGITAL OWNERSHIP, FINANCIAL CRIME, COLLECTIVE ORGANIZATIONS, AND CONSUMER PROTECTION - Revolidis, Ioannis (International Journal of Law in Changing World, 2023)
The editorial for the special issue on NFTs.